Self-Organising Processes and Fractal Approach to the Formation of Non-Crystalline States - Mar’yan, M. I.; Yurkovych, N. V. (Physics and Chemistry of Solid State, 2015)
Shows a description of the fractal structure to the non-crystalline state using the system non-linear dynamic equations, which takes into account the flow of negative entropy of the surrounding environment and the fraction of atoms in soft configuratons. Based on the investigation for the study of non-crystalline materials and the transition to non-crystalline state of the possibility fractal approach to describe them.